Extralinguistic factors influencing Indonesian language learning in France - Isyudanto, Protasius; Laksman-Huntley, Myrna (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2025)
The Indonesian language is becoming increasingly important globally, creating a growing demand for its instruction, including in France. However, learners often face difficulties due to interference between their mother tongue and the Indonesian language they are learning. While some papers offered solutions to overcome these difficulties, these have tended to concentrate on the linguistic aspects and have overlooked the extralinguistic aspects. This paper seeks to address the issue by examining the extralinguistic aspects found in recordings of 10 Indonesian sentences containing phonemes expected to trigger pronunciation errors and spoken by three Malay-Indonesian studies students from different academic years at the Institut National des Langues et Civilisations Orientales (INALCO), from three different college levels. The data was collected through three separate interviews, including the recording of the aforementioned sentences and a discussion about the subjects’ linguistic background. The result was then examined to highlight the extralinguistic and linguistic factors affecting the production of interference. Afterwards, this paper then offers pedagogical suggestions. The study mainly uses phonemic interference and language learning theory, as well as theories related to the psychological and socio-cultural aspects of language learning. This research found that motivation and learning strategy are the two most important variables in the psychological aspect, while input and feedback are the most important aspects in the socio-cultural aspect. Nevertheless, the most decisive factor in Indonesian mastery is the duration of learning.